A book of days - Smith, Patti (Random House, 2022)
"With more than 365 photographs that take you through a single year, A Book of Days is a new way to experience the expansive mind of the visionary poet, writer, and performer. Hopeful, elegiac, playful-and complete with an introduction by Smith that explores her documentary process -A Book of Days is a deeply generous and inspirational map of an artist's life" --